High-strength lightweight concrete containing hollow glass beads and preparation method thereof

By modifying hollow glass microbeads and other materials, high-strength lightweight concrete is prepared, which solves the problem of poor strength of existing lightweight concrete and achieves a comprehensive improvement of low density, high strength and durability.

CN119613030APending Publication Date: 2025-03-14CHINA FIRST HIGHWAY ENGINEERING CO LTD +2

Patent Information

Application Number
CN202510030352.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lightweight concrete has poor strength, high water absorption, easy to crack, and low overall structural strength, which affects its application.

Method used

By activating and modifying hollow glass microbeads, combining the modification of carbon fiber and rubber particles, high-strength lightweight concrete containing hollow glass microbeads is prepared using scientific and reasonable ratios and process flow.

Benefits of technology

It realizes concrete with low density, light weight and high strength, improves the durability and crack resistance of concrete, and significantly improves its application performance in high-rise buildings and large-span bridges and other projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005233959080000161
    Figure BDA0005233959080000161
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses high-strength lightweight concrete containing hollow glass beads and a preparation method of the high-strength lightweight concrete. The high-strength lightweight concrete containing the hollow glass beads is prepared from cement, fly ash, carbon fiber grafted hollow glass beads, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and a water reducing agent according to the mass ratio of (58-75): (25-38): (45-65): (20-40): (42-55): (35-55): (5-12) through mixing, mold filling, vibration molding, covering and demolding. The addition amount of the hollow glass beads is strictly controlled, the influence on the overall strength of the concrete is avoided, the density and weight of the concrete are reduced due to the addition of the light sand and the hollow glass beads, the compactness and integrity of the concrete are improved due to the synergistic effect of the two added fibers, and the raw materials have excellent cohesiveness; the concrete can effectively absorb and disperse stress, and has the advantages of excellent strength, light weight, good durability and excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to high-strength lightweight concrete containing hollow glass microspheres and a preparation method thereof. Background Art

[0002] As one of the most widely used building materials, concrete has the advantages of wide sources and simple production process. Ordinary concrete is mainly made of cement, water, sand, gravel and admixtures in a certain proportion and mixed. Ordinary concrete has high density and heavy weight, which can easily generate large loads on the foundation and structure of the building, increasing the complexity of construction and design. It also has high energy consumption during transportation and construction, low tensile strength, and is prone to small cracks and local damage with the increase of service life. It has poor durability and is difficult to meet the needs of certain special projects. With the continuous development of modern construction technology, the performance requirements for concrete are getting higher and higher. High-strength lightweight concrete has the characteristics of low density, high compressive strength and good durability, making it an ideal choice for high-rise buildings, large-span bridges and other projects.

[0003] Existing lightweight concrete has high water absorption, is easy to crack, and has low overall structural strength, which affects the application of lightweight concrete. Hollow glass microspheres are a new type of material with wide applications and excellent performance developed in recent years. They have the characteristics of light weight, high compressive strength, low thermal conductivity, good thermal insulation effect, and resistance to chemical corrosion. They are widely used in lightweight concrete. Chinese patent application CN115650676A discloses a lightweight high-strength concrete mixture and a preparation method thereof. The concrete mixture includes cement, fly ash, silica ash, mineral powder, fly ash floating beads, vitrified microspheres, shale ceramsite, clay ceramsite, water reducer, and water. The fly ash floating beads and vitrified microspheres, shale ceramsite and clay ceramsite are matched to reduce the volume density of concrete and achieve the lightweight of concrete. However, the dispersion between the raw materials of the concrete is poor, and it is easy to agglomerate and stratify, which reduces the durability and strength of the concrete. Chinese patent application CN116655324A has just disclosed a lightweight high-strength concrete material and a preparation method thereof. The lightweight high-strength concrete material includes cement, silica fume, sawdust, fly ash floating beads, hollow glass microspheres, fly ash coarse ash, ceramsite, water, and a water reducer. The obtained concrete has high strength and low water absorption, but the dispersibility between the raw materials is poor, there are certain defects, and the comprehensive performance of the concrete is affected.

[0004] Therefore, it is of great significance to develop a lightweight and high-strength concrete material. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies in the prior art, the present invention provides a high-strength lightweight concrete containing hollow glass microspheres and a preparation method thereof, which solves the problem of poor strength of lightweight concrete and provides a concrete with low density, light weight and high strength.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the present invention discloses a method for preparing high-strength lightweight concrete containing hollow glass microspheres, comprising the following steps:

[0009] Step 1, after the hollow glass microspheres are activated, they are dispersed in an ethanol solution, after being evenly dispersed, γ-aminopropyltriethoxysilane is added, heated, stirred and mixed, and reacted, after the reaction is completed, filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 h to obtain aminated hollow glass microspheres;

[0010] Step 2: Evenly mix the carbon fiber and N,N-dimethylformamide, add 1,8-diisocyanate and dibutyltin dilaurate, heat, stir and mix in a nitrogen atmosphere to react, and after the reaction is completed, filter, wash with anhydrous ethanol, and vacuum dry at 60° C. for 12 hours to obtain modified carbon fiber;

[0011] Step 3: Evenly mix N,N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers, heat them up, react them, and after the reaction is completed, filter them, wash them with N,N-dimethylformamide, and dry them at 80° C. for 12 hours to obtain carbon fiber grafted hollow glass microspheres;

[0012] Step 4: Activate the rubber particles to obtain activated rubber particles. Disperse the activated rubber particles into an ethanol solution. After uniform dispersion, add γ-glycidyloxypropyltrimethoxysilane, stir and mix to react. After the reaction is completed, filter, wash with anhydrous ethanol, and dry at 60° C. for 12 hours to obtain epoxy-modified rubber particles.

[0013] Step 5: Evenly mix acetone, epoxy-modified rubber particles and itaconic acid, react in a nitrogen atmosphere, and after the reaction is completed, filter, wash with anhydrous ethanol, and dry at 60° C. for 12 h to obtain olefin-modified rubber particles;

[0014] Step 6: Ultrasonically disperse the olefin-modified rubber particles in an ethanol solution, add polypropylene fiber and acrylic acid after uniform dispersion, mix well, add an initiator, react, and after the reaction is completed, filter, wash with deionized water, and vacuum dry at 60° C. for 12 hours to obtain polypropylene fiber grafted rubber particles;

[0015] Step seven, mix cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water for 8-12 minutes to obtain a slurry, then add polypropylene fiber grafted rubber particles and water reducer, stir and mix for 10-20 minutes, the speed is 400-500r / min, discharge, mold, vibrate to form, cover, and demold to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0016] Preferably, in the step 1, the mass ratio of the hollow glass microspheres after activation treatment, the ethanol solution, and γ-aminopropyltriethoxysilane is 100:8000-8500:50-60.

[0017] Preferably, the specific steps of activating the hollow glass microspheres in step one are as follows: mixing the hollow glass microspheres and deionized water evenly, stirring at room temperature for 4 hours, filtering with suction, drying in a drying oven at 60°C for 24 hours, and then mixing with a sodium hydroxide solution with a mass ratio of 5 times, stirring at 80°C for 2 hours, and performing a hydroxylation treatment, wherein the concentration of the sodium hydroxide solution is 0.3 mol / L. After the treatment is completed, filtering with suction, washing with deionized water until the pH of the filtrate is neutral, and vacuum drying at 60°C for 12 hours to complete the activation treatment.

[0018] Preferably, the reaction temperature in step 1 is 80-90° C., and the reaction time is 5-8 h.

[0019] Preferably, the ethanol solution in step 1 is an ethanol aqueous solution with a volume concentration of 50%.

[0020] Preferably, in the step 2, the mass ratio of carbon fiber, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2400-3200:42-55:0.5-1.

[0021] Preferably, the reaction temperature in step 2 is 75-85° C., and the reaction time is 2-4 h.

[0022] Preferably, in the step three, the mass ratio of N,N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers is 3800-4200:100:60-80.

[0023] Preferably, the reaction temperature in step 3 is 95-105° C., and the reaction time is 3-5 h.

[0024] Preferably, the ethanol solution in step 4 is an ethanol aqueous solution with a volume concentration of 75%.

[0025] Preferably, in step 4, the mass ratio of the activated rubber particles, the ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:5500-6500:5-12.

[0026] Preferably, the reaction temperature in step 4 is 55-65° C., and the reaction time is 1-2 h.

[0027] Preferably, the step of activating the rubber particles in step 4 is as follows: washing the rubber particles with deionized water, wherein the mass ratio of deionized water to rubber particles is 1000:100; after washing, filtering and air-drying; and then soaking the rubber particles with sodium hydroxide solution, wherein the concentration of the sodium hydroxide solution is 15%, and the mass ratio of the sodium hydroxide solution to the rubber particles is 800:100; after soaking for 48 hours, filtering and washing with deionized water, and air-drying to obtain activated rubber particles.

[0028] Preferably, in step five, the mass ratio of acetone, epoxy-modified rubber particles and itaconic acid is 1800-2100:100:75-105.

[0029] Preferably, the reaction temperature in step 5 is 50-60° C., and the reaction time is 6-9 h.

[0030] Preferably, in step six, the mass ratio of olefin-modified rubber particles, ethanol solution, polypropylene fiber, acrylic acid, and initiator is 100:1200-1500:55-80:7-10:1-2.

[0031] Preferably, the reaction temperature in step six is ​​35-45° C., and the reaction time is 2-4 h.

[0032] Preferably, the ethanol solution in step six is ​​an ethanol aqueous solution with a volume concentration of 10%.

[0033] Preferably, the initiator in step six is ​​dicumyl peroxide.

[0034] Preferably, in step seven, the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles, and water reducer is 58-75:25-38:45-65:20-40:42-55:35-55:5-12.

[0035] Preferably, the water reducing agent in step seven is a polycarboxylate water reducing agent.

[0036] A high-strength lightweight concrete containing hollow glass microspheres is prepared by adopting the method for preparing the high-strength lightweight concrete containing hollow glass microspheres.

[0037] (III) Beneficial technical effects

[0038] In the present invention, after the hollow glass microspheres are activated, they are modified using γ-aminopropyltriethoxysilane, and amino groups are introduced on the surface of the hollow glass microspheres to obtain aminated hollow glass microspheres. Carbon fibers are modified using 1,8-diisocyanate to obtain modified carbon fibers, and isocyanate groups are introduced on the carbon fibers. The introduced alkyl long chains can improve the toughness of concrete. The isocyanate groups on the modified carbon fibers react with the amino groups on the aminated hollow glass microspheres to obtain carbon fiber grafted hollow glass microspheres. After the rubber particles are activated, they are modified using γ-glycidyloxypropyltrimethoxysilane, and epoxy groups are introduced on the surface of the rubber particles to obtain epoxy-modified rubber particles. The epoxy groups on the epoxy-modified rubber particles undergo a ring-opening reaction with the carboxyl groups in itaconic acid, and hydroxyl groups, carboxyl groups and alkenyl groups are introduced to obtain alkenyl-modified rubber particles. The olefin-modified rubber particles are polymerized with polypropylene fibers and acrylic acid under the action of an initiator to obtain polypropylene fiber-grafted rubber particles. The polypropylene fiber-grafted rubber particles contain a large number of carboxyl groups, which can react with water molecules to form a lubricating layer in the concrete, significantly improving the fluidity and pumpability of the concrete. At the same time, they can also react with Ca in cement. 2+ The complex is formed to generate interaction force between cement particles, thereby improving the strength and durability of concrete. Cement, fly ash, carbon fiber grafted hollow glass microspheres, light sand, polypropylene fiber grafted rubber particles, and water reducer are used as raw materials, and deionized water is mixed, molded, vibrated, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0039] The main components of cement in the present invention are silicate and aluminate, which, as one of the most important materials in concrete, form a bonding force with sand, fiber, etc. in concrete to generate hardened cement glue, making the concrete strong, increasing the strength, and having a certain load-bearing capacity. At the same time, the cement fills the gaps, improves the density and durability of the concrete, prevents the steel bars in the concrete from rusting, controls shrinkage, and reduces the risk of cracking.

[0040] As a mineral admixture, fly ash can effectively reduce the cost of concrete and save energy. The active alumina and silicate components contained in fly ash can form a variety of hardening products in concrete, improving the compressive strength and toughness of the mortar. At the same time, it can be filled between aggregates to make the concrete structure tighter, affecting the setting time and hydration reaction of cement, improving the later strength of concrete, inhibiting alkali-aggregate reaction, and improving the durability of concrete.

[0041] As a kind of aggregate, lightweight sand can reduce the density and weight of concrete, increase the toughness and stability of concrete, maintain a certain strength and durability, improve the workability of concrete, and make concrete easier to construct and shape.

[0042] Hollow glass microspheres have tiny particle shapes and hollow structures, which can fill tiny gaps inside concrete, reduce porosity, and increase the density of concrete, thereby enhancing the overall strength of concrete. Furthermore, the addition of hollow glass microspheres can significantly reduce the density and weight of concrete, reducing the overall load of the building. Carbon fiber has stable chemical properties, high elastic modulus, and excellent tensile strength. It can improve the tensile and compressive strength and crack resistance of concrete, prevent the expansion of microcracks inside concrete, and prevent the occurrence and development of macro cracks, which can further improve the mechanical properties and durability of concrete.

[0043] Polypropylene fiber has the characteristics of high strength, light weight, and non-absorbent. It can increase the fiber content of concrete, effectively control the microcracks caused by factors such as plastic shrinkage, shrinkage, and temperature changes in concrete, prevent and inhibit the formation and development of original cracks in concrete, and play a role in crack prevention, anti-seepage, and anti-abrasion, improving the crack resistance of concrete and the continuity of the concrete medium after hardening. Rubber particles have a large deformation capacity and can play a filling role in concrete, forming a continuous supporting structure in concrete. At the same time, they have high energy absorption and transmission capabilities, which can increase the ductility and crack resistance of concrete, thereby improving the mechanical properties and durability of concrete. The use of rubber particles can also effectively process waste tires, reduce environmental pollution, and reduce the mining of natural aggregates, reducing damage to the environment. The two work together to increase the toughness of concrete, enabling it to better resist external impact and fatigue, and improve the durability of concrete.

[0044] Polycarboxylate water reducer can adsorb on the surface of cement and sand in concrete to form a dispersant covering layer, thereby reducing the water-cement ratio, improving the fluidity of the composite material, forming high molecular polymers in the concrete, improving the friction resistance between concrete particles, and thus reducing the viscosity and cohesion of the concrete.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The present invention strictly controls the amount of hollow glass microspheres added through scientific and reasonable proportions to avoid affecting the overall strength of concrete. By modifying the hollow glass microspheres, the agglomeration of the hollow glass microspheres is effectively avoided, and the hollow glass microspheres can be evenly dispersed in the concrete matrix to avoid stratification. Further, the interfacial bonding force between the hollow glass microspheres and the concrete matrix is ​​improved, and under the action of long-term load or environmental erosion, microcracks or peeling phenomena are reduced, thereby increasing the service life of the concrete and improving the durability of the concrete. The addition of lightweight sand and hollow glass microspheres reduces the density and weight of the concrete, making it lightweight. The rubber particles are modified to effectively avoid the agglomeration of the rubber particles, and can be evenly dispersed in the concrete, thereby improving the impact resistance of the concrete.

[0047] (2) The present invention adds two kinds of fibers, which can reduce the segregation and bleeding of concrete, help disperse the directional stress of concrete, improve the density and integrity of concrete, modify the polypropylene fiber and carbon fiber, avoid the uneven dispersion of the two, and the carbon fiber grafted hollow glass microspheres and polypropylene fiber grafted rubber particles contain a large number of active groups, which can form hydrogen bonds, and the raw materials have excellent adhesion. The two different fibers work synergistically to form a network structure in the concrete through cross-linking, improve the internal pore structure of the concrete, reduce the internal defects of the concrete, improve the density and integrity of the concrete, and have excellent toughness. When the concrete is stretched and impacted by external forces, the evenly distributed fibers can absorb and disperse stress, thereby preventing the expansion of cracks and significantly improving the strength of the concrete. The prepared lightweight concrete has excellent strength, light weight, and good durability. DETAILED DESCRIPTION

[0048] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0049] Example 1

[0050] A method for preparing high-strength lightweight concrete containing hollow glass microspheres comprises the following steps:

[0051] (1) After the hollow glass microspheres are activated, they are dispersed in an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 50%. After the dispersion is uniform, γ-aminopropyltriethoxysilane is added, wherein the mass ratio of the hollow glass microspheres after the activation treatment, the ethanol solution, and the γ-aminopropyltriethoxysilane is 100:8000:50, and the mixture is heated, stirred, and reacted at 80° C. for 8 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain aminated hollow glass microspheres;

[0052] (2) The carbon fiber and N,N-dimethylformamide were mixed evenly, 1,8-diisocyanate and dibutyltin dilaurate were added, wherein the mass ratio of carbon fiber, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate was 100:2400:42:0.5, heated, stirred and mixed in a nitrogen atmosphere, reacted at 75°C for 4h, after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain modified carbon fiber;

[0053] (3) N, N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers in a mass ratio of 3800:100:60 were mixed uniformly, heated, and reacted at 95°C for 5 hours. After the reaction was completed, the mixture was filtered, washed with N, N-dimethylformamide, and dried at 80°C for 12 hours to obtain carbon fiber grafted hollow glass microspheres;

[0054] (4) activating the rubber particles to obtain activated rubber particles, dispersing the activated rubber particles into an ethanol solution having a volume concentration of 75% ethanol aqueous solution, adding γ-glycidyloxypropyltrimethoxysilane after uniform dispersion, wherein the mass ratio of the activated rubber particles, the ethanol solution, and the γ-glycidyloxypropyltrimethoxysilane is 100:5500:5, stirring and mixing, reacting at 55° C. for 2 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60° C. for 12 hours to obtain epoxy-modified rubber particles;

[0055] (5) Acetone, epoxy-modified rubber particles and itaconic acid in a mass ratio of 1800:100:75 were uniformly mixed, reacted at 50° C. in a nitrogen atmosphere for 9 hours, and after the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain olefin-modified rubber particles;

[0056] (6) ultrasonically dispersing the olefin-modified rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol-water solution with a volume concentration of 10%. After uniform dispersion, polypropylene fibers and acrylic acid are added. After uniform mixing, an initiator dicumyl peroxide is added, wherein the mass ratio of the added olefin-modified rubber particles, ethanol solution, polypropylene fibers, acrylic acid, and dicumyl peroxide is 100:1200:55:7:1. The temperature is raised and a reaction is carried out at 35° C. The reaction time is 4 hours. After the reaction is completed, the mixture is filtered, washed with deionized water, and vacuum dried at 60° C. for 12 hours to obtain polypropylene fiber grafted rubber particles.

[0057] (7) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water are mixed for 8 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer are added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer is 58:25:45:20:42:35:5. The mixture is stirred and mixed for 10 minutes at a speed of 400 r / min, discharged, molded, vibrated into shape, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0058] Example 2

[0059] A method for preparing high-strength lightweight concrete containing hollow glass microspheres comprises the following steps:

[0060] (1) After the hollow glass microspheres are activated, they are dispersed in an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 50%. After the dispersion is uniform, γ-aminopropyltriethoxysilane is added, wherein the mass ratio of the hollow glass microspheres after the activation treatment, the ethanol solution, and the γ-aminopropyltriethoxysilane is 100:8200:55, and the mixture is heated, stirred, and reacted at 85° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain aminated hollow glass microspheres;

[0061] (2) The carbon fiber and N, N-dimethylformamide were mixed evenly, 1, 8-diisocyanate and dibutyltin dilaurate were added, wherein the mass ratio of carbon fiber, N, N-dimethylformamide, 1, 8-diisocyanate and dibutyltin dilaurate was 100:2800:48:0.8, heated, stirred and mixed in a nitrogen atmosphere, reacted at 80°C for 3h, after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain modified carbon fiber;

[0062] (3) N, N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers in a mass ratio of 3900:100:68 were mixed uniformly, heated, and reacted at 100°C for 3.5 hours. After the reaction was completed, the mixture was filtered, washed with N, N-dimethylformamide, and dried at 80°C for 12 hours to obtain carbon fiber grafted hollow glass microspheres;

[0063] (4) activating the rubber particles to obtain activated rubber particles, dispersing the activated rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 75%, and after uniform dispersion, adding γ-glycidyloxypropyltrimethoxysilane, wherein the mass ratio of the activated rubber particles, the ethanol solution, and the γ-glycidyloxypropyltrimethoxysilane is 100:6200:10, stirring and mixing, reacting at 60° C. for 1.5 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60° C. for 12 hours to obtain epoxy-modified rubber particles;

[0064] (5) Acetone, epoxy-modified rubber particles and itaconic acid in a mass ratio of 2000:100:90 were uniformly mixed, reacted at 55° C. in a nitrogen atmosphere for 8 h, and after the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 h to obtain olefin-modified rubber particles;

[0065] (6) ultrasonically dispersing the olefin-modified rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol-water solution with a volume concentration of 10%. After uniform dispersion, polypropylene fibers and acrylic acid are added. After uniform mixing, an initiator dicumyl peroxide is added, wherein the mass ratio of the added olefin-modified rubber particles, ethanol solution, polypropylene fibers, acrylic acid, and dicumyl peroxide is 100:1300:65:8:1.4. The temperature is raised and a reaction is carried out at 40° C. The reaction time is 2.5 h. After the reaction is completed, the mixture is filtered, washed with deionized water, and vacuum dried at 60° C. for 12 h to obtain polypropylene fiber grafted rubber particles.

[0066] (7) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water are mixed for 9 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer are added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer is 70:32:52:30:50:45:7. The mixture is stirred and mixed for 15 minutes at a speed of 450 r / min, discharged, molded, vibrated into shape, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0067] Example 3

[0068] A method for preparing high-strength lightweight concrete containing hollow glass microspheres comprises the following steps:

[0069] (1) After the hollow glass microspheres are activated, they are dispersed in an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 50%. After the dispersion is uniform, γ-aminopropyltriethoxysilane is added, wherein the mass ratio of the hollow glass microspheres after the activation treatment, the ethanol solution, and the γ-aminopropyltriethoxysilane is 100:8200:55, and the mixture is heated, stirred, and reacted at 85° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain aminated hollow glass microspheres;

[0070] (2) The carbon fiber and N, N-dimethylformamide were mixed evenly, 1, 8-diisocyanate and dibutyltin dilaurate were added, wherein the mass ratio of carbon fiber, N, N-dimethylformamide, 1, 8-diisocyanate and dibutyltin dilaurate was 100:2800:48:0.8, heated, stirred and mixed in a nitrogen atmosphere, reacted at 80°C for 3h, after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain modified carbon fiber;

[0071] (3) N, N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers in a mass ratio of 4000:100:75 were mixed uniformly, heated, and reacted at 100°C for 4.5 hours. After the reaction was completed, the mixture was filtered, washed with N, N-dimethylformamide, and dried at 80°C for 12 hours to obtain carbon fiber grafted hollow glass microspheres;

[0072] (4) activating the rubber particles to obtain activated rubber particles, dispersing the activated rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 75%, and after uniform dispersion, adding γ-glycidyloxypropyltrimethoxysilane, wherein the mass ratio of the activated rubber particles, the ethanol solution, and the γ-glycidyloxypropyltrimethoxysilane is 100:6200:10, stirring and mixing, reacting at 60° C. for 1.5 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60° C. for 12 hours to obtain epoxy-modified rubber particles;

[0073] (5) Acetone, epoxy-modified rubber particles and itaconic acid in a mass ratio of 2000:100:90 were uniformly mixed, reacted at 55° C. in a nitrogen atmosphere for 8 h, and after the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 h to obtain olefin-modified rubber particles;

[0074] (6) Ultrasonic dispersion of olefin-modified rubber particles in an ethanol solution, wherein the ethanol solution is an ethanol-water solution with a volume concentration of 10%. After uniform dispersion, polypropylene fiber and acrylic acid are added. After uniform mixing, an initiator dicumyl peroxide is added, wherein the mass ratio of the added olefin-modified rubber particles, ethanol solution, polypropylene fiber, acrylic acid, and dicumyl peroxide is 100:1400:75:9:1.8. The temperature is raised and a reaction is carried out at 40° C. The reaction time is 3.5 h. After the reaction is completed, the mixture is filtered, washed with deionized water, and vacuum dried at 60° C. for 12 h to obtain polypropylene fiber grafted rubber particles;

[0075] (7) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water are mixed for 9 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer are added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer is 70:32:52:30:50:45:7. The mixture is stirred and mixed for 15 minutes at a speed of 450 r / min, discharged, molded, vibrated into shape, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0076] Example 4

[0077] A method for preparing high-strength lightweight concrete containing hollow glass microspheres comprises the following steps:

[0078] (1) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water are mixed for 10 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer are added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer is 70:32:62:30:50:52:9, and the mixture is stirred and mixed for 18 minutes at a speed of 450 r / min, discharged, molded, vibrated into shape, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0079] The preparation method of the carbon fiber grafted hollow glass microspheres and the polypropylene fiber grafted rubber particles in this embodiment is the same as the preparation method of the carbon fiber grafted hollow glass microspheres and the polypropylene fiber grafted rubber particles in Example 3.

[0080] Example 5

[0081] A method for preparing high-strength lightweight concrete containing hollow glass microspheres comprises the following steps:

[0082] (1) After the hollow glass microspheres are activated, they are dispersed in an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 50%. After the dispersion is uniform, γ-aminopropyltriethoxysilane is added, wherein the mass ratio of the hollow glass microspheres after the activation treatment, the ethanol solution, and the γ-aminopropyltriethoxysilane is 100:8500:60, and the mixture is heated, stirred, and reacted at 90° C. for 5 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain aminated hollow glass microspheres;

[0083] (2) The carbon fiber and N,N-dimethylformamide were mixed evenly, 1,8-diisocyanate and dibutyltin dilaurate were added, wherein the mass ratio of carbon fiber, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate was 100:3200:55:1, heated, stirred and mixed in a nitrogen atmosphere, reacted at 85°C for 2h, after the reaction was completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain modified carbon fiber;

[0084] (3) N, N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers in a mass ratio of 4200:100:80 were mixed evenly, heated, and reacted at 105°C for 3 hours. After the reaction was completed, the mixture was filtered, washed with N, N-dimethylformamide, and dried at 80°C for 12 hours to obtain carbon fiber grafted hollow glass microspheres;

[0085] (4) activating the rubber particles to obtain activated rubber particles, dispersing the activated rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol aqueous solution with a volume concentration of 75%, and after uniform dispersion, adding γ-glycidyloxypropyltrimethoxysilane, wherein the mass ratio of the activated rubber particles, the ethanol solution, and the γ-glycidyloxypropyltrimethoxysilane is 100:6500:12, stirring and mixing, reacting at 65° C. for 1 hour, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 60° C. for 12 hours to obtain epoxy-modified rubber particles;

[0086] (5) Acetone, epoxy-modified rubber particles and itaconic acid in a mass ratio of 2100:100:105 were uniformly mixed, reacted at 60° C. in a nitrogen atmosphere for 6 hours, and after the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 60° C. for 12 hours to obtain olefin-modified rubber particles;

[0087] (6) ultrasonically dispersing the olefin-modified rubber particles into an ethanol solution, wherein the ethanol solution is an ethanol-water solution with a volume concentration of 10%. After uniform dispersion, polypropylene fibers and acrylic acid are added. After uniform mixing, an initiator dicumyl peroxide is added, wherein the mass ratio of the added olefin-modified rubber particles, ethanol solution, polypropylene fibers, acrylic acid, and dicumyl peroxide is 100:1500:80:10:2. The temperature is raised and a reaction is carried out at 45° C. The reaction time is 2 h. After the reaction is completed, the mixture is filtered, washed with deionized water, and vacuum dried at 60° C. for 12 h to obtain polypropylene fiber grafted rubber particles.

[0088] (7) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water are mixed for 12 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer are added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer is 75:38:65:40:55:55:12. The mixture is stirred and mixed for 20 minutes at a speed of 500 r / min, discharged, molded, vibrated into shape, covered, and demolded to obtain high-strength lightweight concrete containing hollow glass microspheres.

[0089] Comparative Example 1

[0090] A method for preparing concrete containing hollow glass microspheres comprises the following steps:

[0091] (1) Cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water were mixed for 10 minutes to obtain a slurry, and rubber particles, polypropylene fibers and polycarboxylic acid water reducer were added, wherein the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, rubber particles, polypropylene fibers and polycarboxylic acid water reducer was 70:32:62:30:50:30:22:9, and the mixture was stirred and mixed for 18 minutes at a speed of 450 r / min, and the mixture was discharged, molded, vibrated into shape, covered and demolded to obtain concrete containing hollow glass microspheres.

[0092] The preparation method of the carbon fiber grafted hollow glass microspheres is the same as the preparation method of the carbon fiber grafted hollow glass microspheres in Example 4.

[0093] Comparative Example 2

[0094] A method for preparing concrete containing hollow glass microspheres comprises the following steps:

[0095] (1) Cement, fly ash, hollow glass microspheres, carbon fiber, lightweight sand and deionized water were mixed for 10 minutes to obtain a slurry, and polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer were added, wherein the mass ratio of cement, fly ash, hollow glass microspheres, carbon fiber, lightweight sand, deionized water, polypropylene fiber grafted rubber particles and polycarboxylic acid water reducer was 70:32:36:26:30:50:52:9, and the mixture was stirred and mixed for 18 minutes at a speed of 450 r / min, and the mixture was discharged, molded, vibrated, covered and demolded to obtain concrete containing hollow glass microspheres.

[0096] The preparation method of the polypropylene fiber grafted rubber particles is the same as the preparation method of the polypropylene fiber grafted rubber particles in Example 4.

[0097] Comparative Example 3

[0098] A method for preparing concrete containing hollow glass microspheres comprises the following steps:

[0099] (1) Cement, fly ash, hollow glass microspheres, carbon fiber, lightweight sand and deionized water were mixed for 10 minutes to obtain a slurry, and rubber particles, polypropylene fiber and polycarboxylic acid water reducer were added, wherein the mass ratio of cement, fly ash, hollow glass microspheres, carbon fiber, lightweight sand, deionized water, rubber particles, polypropylene fiber and polycarboxylic acid water reducer was 70:32:36:26:30:50:30:22:9, and the mixture was stirred and mixed for 18 minutes at a speed of 450 r / min, and the mixture was discharged, molded, vibrated, covered and demolded to obtain concrete containing hollow glass microspheres.

[0100] The specific steps of activating the hollow glass microspheres in the embodiments and comparative examples of the present invention are as follows: the hollow glass microspheres and deionized water are mixed evenly, stirred at room temperature for 4 hours, filtered, dried in a drying oven at 60°C for 24 hours, and then mixed with a sodium hydroxide solution with a mass ratio of 5 times, stirred at 80°C for 2 hours, and hydroxylated, wherein the concentration of the sodium hydroxide solution is 0.3 mol / L. After the treatment is completed, filtered, washed with deionized water until the pH of the filtrate is neutral, and vacuum dried at 60°C for 12 hours, the activation treatment is completed.

[0101] The steps of activating the rubber particles in the embodiments and comparative examples of the present invention are as follows: washing the rubber particles with deionized water, wherein the mass ratio of deionized water to the rubber particles is 1000:100, after washing, filtering, air-drying, and then soaking the rubber particles with a sodium hydroxide solution, wherein the concentration of the sodium hydroxide solution is 15%, and the mass ratio of the sodium hydroxide solution to the rubber particles is 800:100, after soaking for 48 hours, filtering, washing with deionized water, and air-drying to obtain activated rubber particles.

[0102] The hollow glass microspheres in the embodiments and comparative examples of the present invention were purchased from Shanxi Hainuo Technology Co., Ltd., model HN40, with a particle size of 20 μm; the rubber particles were purchased from Sichuan Huayi Co., Ltd., with a particle size of 2 mm; the carbon fiber was purchased from Lianyungang Zhongfu Shenying Carbon Fiber Co., Ltd., with a diameter of 7 μm and a length of 1 mm; the polypropylene fiber was purchased from Beijing Wantuming Technology Co., Ltd., with a diameter of 20 μm and a product number of 20200405; the cement was purchased from Jiangnan Onoda Cement Co., Ltd., P·Ⅱ52.5 cement, with a density of 3.17 g / cm 3 , specific surface area 388m 2 / kg; fly ash was purchased from the fly ash plant of Shenyang Power Plant and was Grade II fly ash; the lightweight sand was expanded perlite purchased from Houpu Mining Materials Factory with a particle size of 2-4mm; the water reducer was purchased from Tianjin Feilong Concrete Admixture Co., Ltd. and was a polycarboxylic acid water reducer, model TFL-2 polycarboxylic acid high performance water reducer; other raw materials and reagents not specified were commercially available.

[0103] The concrete prepared in Examples 1-5 and Comparative Examples 1-3 was subjected to relevant performance tests, as follows:

[0104] (1) Strength test: The concrete was made into 10cm×10cm×400cm concrete blocks, cured for 28 days, and its flexural strength was measured; the concrete was made into 10cm×10cm×10cm concrete blocks, cured for 28 days, and its compressive strength was measured; the test standards for flexural strength and compressive strength refer to the provisions of GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete";

[0105] (2) Density test: The density of concrete is tested. The test standard refers to the dry apparent density test method in the Technical Specification for Lightweight Aggregate Concrete (JGJ51-2002), and the crushed specimen drying method is used for determination;

[0106] The above test results are shown in Table 1:

[0107] Table 1

[0108]

[0109] According to the test results in Table 1, it can be seen that the concrete corresponding to Examples 1-5 of the present invention has high strength, excellent compressive strength and flexural strength, excellent mechanical properties, low density, and light weight. In Example 4, the 28d flexural strength of the concrete prepared by scientific and reasonable proportioning can reach 34.7MPa, and the 28d compressive strength is 66.5MPa. In Comparative Example 1, rubber particles and polypropylene fibers are directly used instead of polypropylene fiber grafted rubber particles, and in Comparative Example 2, hollow glass microspheres and carbon fibers are directly used instead of carbon fiber grafted hollow glass microspheres. The mechanical properties are greatly affected. Due to the poor dispersibility and compatibility between the raw materials, the density of the concrete is reduced and the density is reduced. In Comparative Example 3, the rubber particles, polypropylene fibers, hollow glass microspheres, and carbon fibers are not modified. The rubber particles, polypropylene fibers, hollow glass microspheres, and carbon fibers are added to the concrete as raw materials. The compatibility and dispersibility between the raw materials are poor, and the strength of the prepared concrete is greatly reduced.

[0110] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing high-strength lightweight concrete containing hollow glass microspheres, characterized in that: The following steps are involved: Step 1, after the hollow glass microspheres are activated, they are dispersed in an ethanol solution, after being evenly dispersed, γ-aminopropyltriethoxysilane is added, heated, stirred and mixed, and reacted, after the reaction is completed, filtered, washed, and dried at 60° C. for 12 h to obtain aminated hollow glass microspheres; Step 2: Evenly mix the carbon fiber and N,N-dimethylformamide, add 1,8-diisocyanate and dibutyltin dilaurate, heat, stir and mix in a nitrogen atmosphere to react, and after the reaction is completed, filter, wash, and vacuum dry at 60° C. for 12 hours to obtain modified carbon fiber; Step 3: Evenly mix N,N-dimethylformamide, aminated hollow glass microspheres, and modified carbon fibers, heat them up, react them, and after the reaction is completed, filter them, wash them, and dry them at 80° C. for 12 hours to obtain carbon fiber grafted hollow glass microspheres; Step 4, activating the rubber particles to obtain activated rubber particles, dispersing the activated rubber particles into an ethanol solution, adding γ-glycidyloxypropyltrimethoxysilane after uniform dispersion, stirring and mixing, reacting, and filtering after the reaction is completed, washing, and drying at 60° C. for 12 hours to obtain epoxy-modified rubber particles; Step 5: Evenly mix acetone, epoxy-modified rubber particles and itaconic acid, react in a nitrogen atmosphere, and after the reaction is completed, filter, wash, and dry at 60° C. for 12 hours to obtain olefin-modified rubber particles; Step 6: Ultrasonically disperse the olefin-modified rubber particles in an ethanol solution, add polypropylene fiber and acrylic acid after uniform dispersion, mix well, add an initiator, react, and after the reaction is completed, filter, wash, and vacuum dry at 60° C. for 12 hours to obtain polypropylene fiber grafted rubber particles; Step seven, mix cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand and deionized water for 8-12 minutes to obtain a slurry, then add polypropylene fiber grafted rubber particles and water reducer, stir and mix for 10-20 minutes, the speed is 400-500r / min, discharge, mold, vibrate to form, cover, and demold to obtain high-strength lightweight concrete containing hollow glass microspheres.

2. The method for preparing a high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step 1, the mass ratio of the hollow glass microspheres after activation treatment, the ethanol solution, and γ-aminopropyltriethoxysilane is 100:8000-8500:50-60, the reaction temperature is 80-90° C., and the reaction time is 5-8 hours.

3. The method for preparing a high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step 2, the mass ratio of carbon fiber, N,N-dimethylformamide, 1,8-diisocyanate and dibutyltin dilaurate is 100:2400-3200:42-55:0.5-1, the reaction temperature is 75-85°C, and the reaction time is 2-4h.

4. The method for preparing a high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step 3, the mass ratio of N,N-dimethylformamide, aminated hollow glass microspheres and modified carbon fibers is 3800-4200:100:60-80, the reaction temperature is 95-105° C., and the reaction time is 3-5 hours.

5. The method for preparing high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step 4, the mass ratio of the activated rubber particles, the ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:5500-6500:5-12, the reaction temperature is 55-65° C., and the reaction time is 1-2 h.

6. The method for preparing high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step 5, the mass ratio of acetone, epoxy-modified rubber particles and itaconic acid is 1800-2100:100:75-105, the reaction temperature is 50-60° C., and the reaction time is 6-9 hours.

7. The method for preparing high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step six, the mass ratio of olefin-modified rubber particles, ethanol solution, polypropylene fiber, acrylic acid, and initiator is 100:1200-1500:55-80:7-10:1-2, the reaction temperature is 35-45° C., and the reaction time is 2-4 hours.

8. The method for preparing high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: The initiator in step six is ​​dicumyl peroxide.

9. The method for preparing high-strength lightweight concrete containing hollow glass microspheres according to claim 1, characterized in that: In the step seven, the mass ratio of cement, fly ash, carbon fiber grafted hollow glass microspheres, lightweight sand, deionized water, polypropylene fiber grafted rubber particles, and water reducing agent is 58-75:25-38:45-65:20-40:42-55:35-55:5-12.

10. A high-strength lightweight concrete containing hollow glass microspheres prepared by the method for preparing high-strength lightweight concrete containing hollow glass microspheres according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lightweight high-strength ceramsite concrete mixture and preparation method thereof

    CN115650676A

  • Lightweight high-strength concrete material and preparation method thereof

    CN116655324A

Cited By

  • Premixed high-strength flow-state solidified soil and preparation method thereof

    CN120328979A

  • Premixed high-strength fluidized solidified soil and preparation method thereof

    CN120328979B

  • High-impermeability regenerated micro-powder concrete and preparation method thereof

    CN120887693A

  • Calcium silicate hydrate modified hollow glass bead concrete and preparation method thereof

    CN120965210A

  • Green cast-in-place high-strength lightweight foam concrete

    CN121021078A